PENGARUH STRATEGI BISNIS TERHADAP KEBERHASILAN USAHA - Nur Pratama, Mochamad Nizar Januar (Business Education Program of Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to determine the perception of Persib Fans Club merchandise store entrepreneurs regarding the implementation of business strategies and business success. A survey was conducted at the Persib Fans Club merchandise store in Bandung with a population of 21 entrepreneurs. The results of the study using a questionnaire revealed that the description of the business strategy of the Persib Fans Club merchandise store entrepreneur in the city of Bandung is in the quite good category, it can be said that most of respondents can implement business strategies better so that business success is getting better. Entrepreneurs at the SMEs scale are expected to implement more intensive business strategies so as to increase business success.